Harmonization and Tuning: Integrating Africa - Hahn, Karola; Teferra, Damtew (International Higher Education, 2012)
Tuning, the European Union's effort to harmonize academic coursework in several field is of much interest and relevance to Africa. This article discusses current thinking and efforts in Africa to conceptualize and implement tuning arrangements in the African context.